Efektivitas latihan senam poundfit high-intensity interval training (HIIT) terhadap kualitas tidur pada dewasa muda sedentary lifestyle - Isaura, Gionovie Khalisha; Rahmi, Upik; Rohaedi, Slamet; Wahdini, Ridha (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Sleep quality disturbances are highly prevalent among young adults and are closely associated with sedentary behavior, defined as waking activities performed in a sitting or reclining position with low energy expenditure for prolonged periods. Among university students, sedentary time exceeding 7 hours per day has been linked to poorer sleep quality. Although high-intensity physical activity is known to improve sleep quality, evidence regarding music-based High-Intensity Interval Training (HIIT), such as poundfit, remains limited. Purpose: To examine the effectiveness of poundfit-based HIIT on sleep quality among sedentary young adults. Methods: A quasi-experimental design with a pretest-posttest control group. A total of 40 female participants with high sedentary time, defined as more than 7 hours per day spent sitting or reclining while awake, were assessed using the Sedentary Behavior Questionnaire (SBQ). Participants were allocated into an intervention group (n = 20) and a control group (n = 20). The intervention group participated in poundfit-based HIIT sessions three times per week for four weeks, with each session lasting 45-60 minutes. Sleep quality was measured using the Indonesian version of the Pittsburgh Sleep Quality Index (PSQI), which has demonstrated good validity and reliability, with Cronbach’s alpha of 0.741. Data were analyzed using the Wilcoxon test, independent sample t-test, and effect size calculation. Results: The intervention group showed a significant reduction in PSQI scores from 8.35 ± 2.21 to 4.15 ± 2.18 (p < 0.001; r = 0.85), while the control group showed no significant change (p = 0.198). A significant difference in PSQI score changes was found between the intervention and control groups (p = 0.001). Conclusion: Poundfit-based HIIT is effective in improving sleep quality among young adults with high sedentary behavior of more than 7 hours per day. This intervention may serve as a practical and clinically meaningful physical activity program. Suggestion: Poundfit-based HIIT as a structured physical activity to improve sleep quality among university students with a sedentary lifestyle. The program can be effectively performed three times per week for four weeks, with a duration of 45-60 minutes per session. For less optimal outcomes, additional light-to-moderate physical activity, sleep hygiene education, and stress management are recommended. This intervention is considered more applicable and motivating for university students than conventional physical exercise in the context of promotive nursing care. Keywords: High-Intensity Interval Training (HIIT); Poundfit; Sedentary Behavior; Sleep Quality; Young Adults. Pendahuluan: Gangguan kualitas tidur banyak terjadi pada dewasa muda dan berkaitan erat dengan perilaku sedentari, yaitu aktivitas saat terjaga yang dilakukan dalam posisi duduk atau berbaring dengan pengeluaran energi rendah dalam waktu yang lama. Pada mahasiswa, waktu sedentari lebih dari 7 jam per hari telah dikaitkan dengan kualitas tidur yang lebih buruk. Meskipun aktivitas fisik intensitas tinggi diketahui dapat meningkatkan kualitas tidur, bukti mengenai latihan High-Intensity Interval Training (HIIT) berbasis musik, seperti poundfit, masih terbatas. Tujuan: Untuk mengetahui efektivitas latihan poundfit berbasis HIIT terhadap kualitas tidur pada dewasa muda dengan gaya hidup sedentary. Metode: Penelitian desain kuasi-eksperimen dengan rancangan pretest-posttest control group. Sebanyak 40 partisipan perempuan dengan waktu sedentari tinggi, yaitu lebih dari 7 jam per hari dalam posisi duduk atau berbaring saat terjaga, dinilai menggunakan Sedentary Behavior Questionnaire (SBQ). Partisipan dibagi menjadi kelompok intervensi (n = 20) dan kelompok kontrol (n = 20). Kelompok intervensi mengikuti latihan poundfit berbasis HIIT sebanyak 3 kali per minggu selama 4 minggu, dengan durasi 45-60 menit setiap sesi. Kualitas tidur diukur menggunakan Pittsburgh Sleep Quality Index (PSQI) versi bahasa Indonesia yang telah menunjukkan validitas dan reliabilitas baik dengan nilai Cronbach’s alpha sebesar 0.741. Data dianalisis menggunakan uji Wilcoxon, independent sample t-test, dan perhitungan effect size. Hasil: Kelompok intervensi menunjukkan penurunan skor PSQI yang signifikan dari 8.35 ± 2.21 menjadi 4.15 ± 2.18 (p < 0.001; r = 0.85), sedangkan kelompok kontrol tidak menunjukkan perubahan yang signifikan (p = 0.198). Terdapat perbedaan perubahan skor PSQI yang signifikan antara kelompok intervensi dan kelompok kontrol (p = 0.001). Simpulan: Latihan poundfit berbasis HIIT efektif dalam meningkatkan kualitas tidur pada dewasa muda dengan perilaku sedentari tinggi lebih dari 7 jam per hari. Intervensi ini dapat menjadi program aktivitas fisik yang praktis dan bermakna secara klinis. Saran: Latihan HIIT berbasis poundfit sebagai aktivitas fisik terstruktur untuk meningkatkan kualitas tidur mahasiswa dengan gaya hidup sedentari. Program ini efektif dilakukan 3 kali seminggu selama 4 minggu dengan durasi 45-60 menit per sesi. Pada hasil yang belum optimal, diperlukan tambahan aktivitas fisik ringan hingga sedang, edukasi sleep hygiene, dan manajemen stres. Intervensi ini dinilai lebih aplikatif dan memotivasi mahasiswa dibandingkan latihan fisik konvensional dalam konteks keperawatan promotif. Kata Kunci: Dewasa Muda; Kualitas Tidur; High-Intensity Interval Training (HIIT); Perilaku Sedentari; Poundfit.